PERANCANGAN STRATEGI PERUSAHAAN MENGGUNAKAN METODE BALANCED SCORECARD DAN HOSHIN KANRI PADA PERUSAHAAN GARMEN - Peribadi, Sylvia Angeline; Kristina, Helena Juliana; Saryatmo, M Agung (Jurnal Mitra Teknik Industri, 2024)
The research was conducted in a garment company which is a manufacturing industry company engaged in garment or clothing. To be able to compete in similar industries, it is important to measure performance to assess the extent to which the company has made progress in the company's success in achieving the targets set. The company has so far only seen from the financial aspect, there has been no comprehensive performance measurement. Performance measurement uses the Balanced Scorecard (BSC) method which consists of 4 perspectives, namely finance, customers, internal business and learning and growth. BSC aims to help companies determine priorities and monitor the company's progress in achieving goals. From these 4 perspectives, each weight is 0.307; 0,260; 0,247; 0,186. In the Objective Matrix (OMAX) method which aims to measure company productivity and Traffic Light System which aims to make it easier to interpret the achievement of company performance obtained from 12 key performance indicators (KPIs) there are 3 KPIs that have reached the target, 5 KPIs that have almost reached the target including increasing profits, increasing customer loyalty, improving good relationships with customers, reduction of product defec, as well as routine employee training and 4 KPIs that are still below the target include adding new customers, reducing work accidents, increasing employee satisfaction and increasing employee discipline. After that, using the Hoshin Kanri Planning X-Matrix method to design strategies so that the company can achieve long-term goals and continue to strive for improvement and growth.